(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to measure the effectiveness of a learning environment based on visual design using Canva AI in developing reading skills among primary stage pupils. A quasi-experimental design with a single group pre-test/post-test approach was employed as the most appropriate methodology for this type of study. The study sample consisted of 20 first-grade pupils from Al-Nakhaba Private Schools in Al-Kharj. A pre-test was administered to assess reading skill levels, followed by instructional implementation using the visual learning environment via Canva AI for a specified duration. Upon completion of the intervention, pupils underwent a post-test to measure achieved improvement. The study revealed statistically significant differences (p ≤ 0.05) between the mean scores of pupils in the pre-test and post-test in favor of the post-test, with an average improvement of 24.20 points (238.4% improvement rate). The effect size (Cohen’s d) reached 2.996, indicating a very large effect according to Cohen’s standards. Pupils were distributed across improvement levels as follows: high improvement (55%), moderate improvement (25%), and low improvement (20%), with all pupils achieving positive improvement. Based on the findings, the study recommends adopting learning environments based on visual design using Canva AI in teaching reading skills at the primary level and training teachers to utilize these tools in designing educational activities.